Possibilities of Capturing Methane from Hard Coal Deposits Lying at Great Depths - Nikodem Szlązak; Justyna Swolkień (Energies, 2021)
Methane present in coal seams is a natural hazard present during the exploitation of underground mining plants. It is an explosive and flammable gas that is released into mining excavations, and it is necessary to reduce its concentration. Capturing methane while preparing extraction is virtually impossible due to the low permeability of coal resulting from its deposition depth. After the beginning of exploitation and disrupting the seam’s structure, methane is released into mine air. The most common method of minimizing gas released into ventilation air is draining the rock mass. This method allows achieving the desired ventilation parameters but requires appropriate mining techniques in hazardous areas. The article presents the example of methane capture during the operation in the longwall B-15 with an overlying drainage gallery. The authors have highlighted an example of the longwall B-15 that when using this particular drainage method, allowed capturing twice the amount of methane forecasted, thus increasing the efficiency of methane drainage. At the preliminary stage of longwall development, the amount of methane charged by the drainage system had relatively low values, reaching 15 m3/min. In the next few months, these parameters increased and varied between 35 to 55 m3/min. A significant difference in methane capture appeared in the second stage of exploitation, where the highest value of captured methane reached 82 m3/min. This particular longwall example shows that it is crucial to properly design the drainage system for seams with high forecasted methane release. It is worth remembering that using a drainage gallery provides an increase in the methane capture from the desorption zone areas, thus increasing total methane capture in comparison to forecasts.